IMPROVING THE RELIABILITY OF INTERNET TIME AND COST EFFICIENCY IN THE GLOBAL INFORMATION FLOW - Hasanudin Hasanudin; Drs. H. Sutirto Sadikin, MA (Jurnal Sistem Informasi, 1996)
The global information needs when users are involved in a high traffic flow information, are usually influenced by social and economic factors.  High-speed access in reaching  a wide network of information is also needed to create an information with limited time. Global information networks is the need for exchange of information Anta individual / organization to another based on various interests of the individual / organization itself or others. It turns out the time and cost efficiency not affect Internet in influencing the range of global information access, internet service user means members will continue to grow while the fixed costs and fixed access time.